The effects of demographic factors and social support on depression among high school teenage mothers in the Mankweng area - Mothapo, Patrick Maredi (University of Limpopo (Turfloop Campus), 2011)
Adolescent motherhood is a major problem in many societies throughout the world. One of the problems these young mothers have to deal with is depression. Depression often results in the disengagement of mother-child interaction. Adolescent mothers who are identified as depressed are more at increased risk of future psychopathology, with additional effects on their future and infants‟ lives. The aim of this study investigates the influence of demographic factors (age and marital status) and social support on depression among high school teenage mothers in the Mankweng area in Limpopo Province, South Africa. Two hundred adolescent mothers took part in the study. One hundred of participants were mothers while the others were non-mothers. Their ages ranged between 15 and 19. A quantitative research design and methodology was employed. Correlation analysis method was also used to associate lack of social support with depression. Correlation analysis indicates that lack of social support was a significant factor negatively affecting teenage mothers‟ disposition to depression (r = -0.609, p < 0.01). T-test analysis which was used to compare the experience of depression among teenage mother base on different age group, indicates that age does not play a significant role for teenage mothers to experience depression (t = 1.409, df = 98; p > 0.05). T-test analysis was also used to compare the experience of depression on married teenage mother and unmarried teenage mothers, and indicates that teenage mothers experience depression irrespective of marital status (t = 1.091, df = 98; p > 0.05). It is recommended that professional counseling be provided to teenage mothers before they return to the school system after giving birth. Support from social welfare and family members are also key support system for the young mothers so that these bring psychological and social stability in their lives.
Thesis (M.A. (Clinical Psychology)) --University of Limpopo, 2011
Keywords: Teenage mothers; Adolescent mothers; 306.8743968; Teenage mothers -- South Africa -- Limpopo Province